2022
DOI: 10.1002/ajpa.24560
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal age at marriage and pregnancy with infant undernutrition: Evidence from first‐time mothers in rural lowland Nepal

Abstract: Objectives: Maternal factors shape the risk of infant undernutrition, however the contributions of age at marriage versus age at pregnancy are rarely disentangled. We explore these issues in a population from lowland rural Nepal, where median ages at marriage and first pregnancy are 15 and 17 years respectively and marriage almost always precedes pregnancy. Methods:We analyzed data on first-time mothers (n = 3002) from a clusterrandomized trial (2012)(2013)(2014)(2015). Exposures were ages at marriage and preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
3
0
2
Order By: Relevance
“…A previous study exhibits a similar relationship between the coexistence of underweight with wasting and stunting and the education of mothers (Khaliq, Wraith, Miller, & Nambiar, 2022 ). This study has shown that the marital age of the mother is significantly associated with child malnutrition which is also corroborated by a survey conducted in rural areas of Nepal (Wells et al, 2022 ). The prevalence of malnutrition among children in the Sylhet division is higher than in any other region of Bangladesh.…”
Section: Discussionsupporting
confidence: 83%
“…A previous study exhibits a similar relationship between the coexistence of underweight with wasting and stunting and the education of mothers (Khaliq, Wraith, Miller, & Nambiar, 2022 ). This study has shown that the marital age of the mother is significantly associated with child malnutrition which is also corroborated by a survey conducted in rural areas of Nepal (Wells et al, 2022 ). The prevalence of malnutrition among children in the Sylhet division is higher than in any other region of Bangladesh.…”
Section: Discussionsupporting
confidence: 83%
“…Maternal factors related to the incidence of stunting include maternal age. Mothers who marry, become pregnant and give birth at a young age may give impacts on the growth of children (Wells et al, 2022). A study conducted in 18 countries in Asia, Africa, and Latin America reveals that in 3 out of 7 countries in Asia and 6 out of 9 countries in Africa there is an effect of mothers who become pregnant and give birth at a young age toward height restriction of children aged 0-11 month.…”
Section: Introductionmentioning
confidence: 99%
“…Di Asia Selatan dan Afrika Timur, pernikahan dini pada perempuan telah diidentifikasi sebagai faktor risiko yang kuat untuk stunting di antara anakanak dalam rentang usia lahir hingga 5 tahun (Efevbera et al, 2017;Khan et al, 2019;Paul et al, 2019). Pernikahan dini dan kehamilan secara langsung berdampak pada pertumbuhan dan status gizi anak, terutama anak sulung (Wells et al, 2022). Hal tersebut mengakibatkan pertumbuhan yang lebih buruk, terutama pada hasil z skor untuk berat badan dan panjang badan, sebab pernikahan dini dan kehamilan dapat meningkatkan berbagai faktor sosial dan biologis yang menyebabkan kekurangan gizi pada anak (Wells et al, 2022).…”
Section: Monitoring Dan Evaluasiunclassified
“…Pernikahan dini dan kehamilan secara langsung berdampak pada pertumbuhan dan status gizi anak, terutama anak sulung (Wells et al, 2022). Hal tersebut mengakibatkan pertumbuhan yang lebih buruk, terutama pada hasil z skor untuk berat badan dan panjang badan, sebab pernikahan dini dan kehamilan dapat meningkatkan berbagai faktor sosial dan biologis yang menyebabkan kekurangan gizi pada anak (Wells et al, 2022). Faktor lainnya yang dapat memengaruhi masalah gizi seperti gizi kurang dan stunting yaitu status sosial-ekonomi rumah tangga yang rendah, status antenatal care ibu, berat badan lahir, dan pendidikan ibu (Yuliana & Hakim, 2019) (Beal et al, 2018).…”
Section: Monitoring Dan Evaluasiunclassified